HUBUNGAN FAKTOR PEMBENTUK PERILAKU DENGAN KEPATUHAN PENGGUNAAN ALAT PELINDUNG TELINGA PADA TENAGA KERJA DI PLTD AMPENAN - Candra, Ahmad (The Indonesian Journal of Occupational Safety and Health, 2015)
ABSTRACTSafe behaviour in company could prevent Noise Induce Hearing Loss. Safe behaviour that could prevent hearing loss isÂ  the compliance of wearing ear protector. It could be shaped by using the activator-behaviour-consequence (ABC) method that can be influenced by forming behaviour factors (knowledge, training, and supervision and positive reinforcement). The aim of this research was to analyze the association between forming behaviour factors with the compliance of wearing ear protector. This was an observational analytic study with cross sectional approach with 18 workers in maintenance section of PLTD Ampenan as sample. Data were collected through questionnaire, interview, and observation. Data were analyzed used pearson chi-square and fisher exact test to obtain the association between variables. The results showed that most of the workers (72.2%) in maintenance section of PLTD Ampenan had the compliance of wearing ear protector. There were significant correlation between knowledge, training, supervision, and positive reinforcement with the compliance of wearing ear protector. Supervision has a very strong correlation (coefficent 1,000). The more workers feel himself under supervision, the better their behaviour will be. It is recommended that the company can perform all forming behaviour factors especially improve the supervision method in order to make all workers have the compliance of wearing ear protector.Keywords: forming behaviour factor, safe behaviour, ABC method